2020
DOI: 10.35631/jthem.518004
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting International Tourist Arrivals in Malaysia Using Sarima and Holt-Winters Model

Abstract: Tourism can be described as the activities of visitors who make a visit to the main destination outside their usual environment for less than a year for any purpose. The tourism industry has become one of the influential sectors in global economic growth. Thus, tourism forecasting plays an important role in public and private sectors concerning future tourism flows. This study is an attempt to determine the best model in forecasting the international tourist's arrival in Malaysia based on Box-Jenkins and Holt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The pandemic has introduced a great deal of uncertainty in all aspects of life. Factors such as the financial speed of policy ARIMA-HOLD OUT For International 1.45% [82] ANN CGK-JOG 1.29% [25] MLP Neural Net (12-2-1) 2.80% [116] SARIMA-SVR Passenger Traffic Volume 2.31% [67] Regression + SVM Model 5.07% [62] Regression prediction 2.30% [33] LSTM 4.00% [72] Holt-Winters SARIMA -Singapore 2.69% Tourism [9,25,31,41,43,65,77,93,112] Revenue Management [61,87] Infrastructure Management [10,13,42,96,100] changes in all sectors impact forecasting passenger demand directly or indirectly. Few studies have found that aviation recovered after the pandemic [52].…”
Section: Forecasting Challenges With Pandemicmentioning
confidence: 99%
“…The pandemic has introduced a great deal of uncertainty in all aspects of life. Factors such as the financial speed of policy ARIMA-HOLD OUT For International 1.45% [82] ANN CGK-JOG 1.29% [25] MLP Neural Net (12-2-1) 2.80% [116] SARIMA-SVR Passenger Traffic Volume 2.31% [67] Regression + SVM Model 5.07% [62] Regression prediction 2.30% [33] LSTM 4.00% [72] Holt-Winters SARIMA -Singapore 2.69% Tourism [9,25,31,41,43,65,77,93,112] Revenue Management [61,87] Infrastructure Management [10,13,42,96,100] changes in all sectors impact forecasting passenger demand directly or indirectly. Few studies have found that aviation recovered after the pandemic [52].…”
Section: Forecasting Challenges With Pandemicmentioning
confidence: 99%
“…Usually, seasonal autoregressive integrated moving average or SARIMA model is a standard method used for modeling the number of tourist arrivals in many researches. Recent research using the SARIMA model includes the study by Hwandee and Phumchusri, (2020) and Lip et al (2020). Nevertheless, to assess the impacts of interrupted incidents or prior known interventions on the number of tourist arrivals, the SARIMA with intervention model is often employed.…”
Section: Literature Reviewmentioning
confidence: 99%